Social movements for good how companies and causes create viral change - Feldmann, Derrick 1978- (Hoboken Wiley, 2016)
"Create real change in the new social movement paradigm Social Movements for Good is a guidebook for driving change, by taking advantage of the social "currency" that makes movements go viral. Author Derrick Feldmann has spent a career showing organizations how to best reach donors, activists, and employees, and engage a new generation of supporters. In this book, he shares his secrets alongside the stories of today's most successful social good movements by companies and nonprofits. You'll learn about the leaders behind these movements, the individuals who responded, and the approaches that made it work. Modern social movements operate within a new paradigm, and this informative guide walks you through how these movements are created, why people get on board, and the strategy and support network that must be in place for it to succeed. Just going viral isn't enough to make a movement successful--there must be a plan, and the right people with the right skills to follow through with the execution. This book shows you who you need on your side, what they need to do their jobs, and which tools and methods are proving most effective every day. Read the stories of today's most successful social good movements Understand how modern social movements are created Learn how to truly activate a new generation of activists and supporters Formulate an approach that makes the public respond to your issue Effective social movements don't arise by accident. People don't spontaneously come together and effect real change. If you want your movement to succeed, you need a solid strategy and the tools to follow through. Social Movements for Good is your roadmap to viral success and the advancement of your cause"--
"Social Movements for Good tells the stories behind five of today's most successful Millennial-generation social good movements by companies and nonprofits. In exploring each movement highlighted in the book, the reader will learn about leaders that created these movements, individuals that responded, and the data and research behind the movement's success. The result is a full understanding of how social good movements are created today, how to truly activate a new generation, and the foundation and approach necessary to generate a public response to a social issue"--
Includes bibliographical references and index.
Keywords: Social movements; Leadership; Nonprofit organizations; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities